Enhanced Terahertz Spectral‐Fingerprint Detection of α‐Lactose Using Sub‐Micrometer‐Gap On‐Chip Waveguides. Issue 3 (7th December 2021) - Park, Sae June; Parker‐Jervis, Rowan S.; Cunningham, John E.
Abstract: We investigate using finite element methods how sub‐micrometer to micrometer‐scale coplanar waveguide (CPW) can be used for the detection of fingerprint spectra of very small (of order 10 −14 mL) volumes of analytes in the terahertz (THz) frequency range. The electric field distribution is investigated near the waveguide for various gap widths between the center conductor and ground plane using a finite element simulation (ANSYS High Frequency Structure Simulator, HFSS). Taking lactose monohydrate as an exemplar material, a Drude–Lorentz model is combined for its real and imaginary permittivities with this numerical simulation, finding a significant enhancement in fingerprint detection as the gap width is reduced; the electric field in the CPW is found to increase by a factor ≈14 times moving from a 20 to 0.5‐µm‐wide gap between center conductor and ground plane, while the on‐resonance THz absorption increases ≈14 times. The effective absorption coefficient of the lactose at 530 GHz is investigated as a function of the slot width for various lactose block thicknesses to understand how change in the field confinement and in the effective overlap between the lactose block and incident THz waves affect the effective absorption coefficient. Abstract : This work develops a novel method for detecting spectral fingerprints of target materials in the terahertz frequency range by introducing sub‐micrometer‐gap coplanar waveguide (CPW) devices. It is shown that the sensitivity per unit volume of lactose can be improved ≈453 times with the CPW device with a 0.5 µm wide slot compared to the device with a 20 µm wide slot.